Síntese quimioenzimática dos intermediários do apremilast via carbamatação, utilizando lipases - Oliveira, Artur Ramon Tomé (2020)
The apremilast, marketed as OTZELA®, is a oral drug, used in psoriases and psoriatic arthritis psoriatic, acting as a anti-inflammatory. Is a recent drug, which was approved for FDA (Food Drug Administration) in 2014. The drug referred have a only stereogenic center and is commercialized in enantiomerically pure form, since what the (S)-enantiomer is more active which the (R)-enantiomer. In this work we describe the preliminary results referred the chemoenzymatic synthesis of apremilast intermediates in lipases presence, being the key-step, the obtaining of amine (S-2)-1-(3-ethoxy-4-methoxyphenyl)-1-methylsulfonyl-2-ethylamine, (S)-36. That intermediate can be obtained through kinetic resolution of amine rac-36, via carbamation reaction using lipases. The amine rac-36 was prepared, as 70% yield, via two sequential steps one-pot, which consisted in 3-ethoxy-4-methoxybenzonitrile, 38, reaction with (methylsulfonyl)methanide (formed carbanion among the dimethylsulfone and n-butyl-lithium), with obtaining of the enamine 1-(3-ethoxy-4-methoxyphenyl)-2-(methylsulfonyl)ethenamine 39, treatment followed with NaBH4, in glacial acetic acid. The 1-(3-ethoxy-4-methoxyfenyl)-2-(mehtylsulfonyl)ethyl)alyl carbamate, rac-49, was prepared starting of amine rac-34 via carbamation reaction with allyl chloroformate, in triethylamine presence, 89% yield. Both, the amine rac-34 and the carbamate rac-49 corresponding was analyzed by CLAE, using a chiral column, and ideal conditions for the enantiomers separation. The first approach to be studied was the lipase behavior in several solvents in 40 ºC for 72 h for kinetic resolution of amine rac-36, via carbamation reaction. Highlighted the solvents which show low value of dielectric constant: THF, TBME, hexane, cyclohexane and toluene, since which the best result was obtained in hexane, in CAL-B presence, as 14% conversion and >200 enantioselectivity (E). Also of CAL-B, the Candida rugosa lipase and CAL-A are promising in kinetic resolution of rac-36. In parallel, the commercial anhydride 3- nitrophthalic anhydride 50, was effectively transforming in 3-aminophthalic, 51, qualitative yield. The latter was subjected to an acetylation reaction to obtain 3-acetylaminophthalic anhydride 37, one of apremilast's intermediates, but with a yield of only 25%.